Arsenic Contents in Some Malaysian Vegetables - She, Low Kun; Kheng, Lee Chnoong (1992)
The arsenic content of forty-one common Malaysian vegetables was analysed by hydride generation-inductively coupled plasma emission spectrometry. None of the samples showed level greater than 2.00 J.1 g {fJ. The highest was found in bean sprouts (Phaseolus radiatus) (2.00 J.1 g {fl) and the lowest in sengkuang (Pachyrrhizus erosus) (0.20 J.1 g {fl). Boiling caused a loss of 17 to 60% arsenic in the plants.